Analisis Undang-Undang Desa - Abdul Fatah Fanani; Wahyu Astutik; Dodik Wahyono; Suprapto Suprapto (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2019)
Policies on villages in Indonesia have experienced ups and downs since the Republic of Indonesia was established. The regulation of the village is urgent because the village has a strategic position in development in Indonesia. Further the existence of villages in Indonesia had already existed before the Indonesian republic was established. In this article, we analyze the policy on villages by making comparisons of some village regulations starting before the republic of Indonesia was established, at the beginning of independence and until now. This research is library research, and the main data comes from book and journal publications available in Indonesia since before independence until post independence. This research is ultimately useful for any policy study on village regulation. The results of the policy analysis on the village law show that several laws and regulations concerning the village in the past have reduced independence and natural conditions of the village. Law number 5 of 1979 has reduced the authenticity and uniqueness of the village from its natural conditions by carrying out uniformity on the form of villages and village government in Indonesia. However, with the enactment of Law number 6 of 2014, the sovereignty, independence and natural conditions of the village are given the right and authority to return to their original natural forms with the recognition of the right to recognize and subsidiarity.